Importance of the game in natural numbre-concept acquisition - Hernández García, Patricia (2017)
Games are a natural and spontaneous function that is essential for the normal development of the child. Because of their affective and creative value, they can be used in the rehabilitation of some specific learning difficulties. Not in vain, and in spite of the numerous changes that the society has been suffering, games have prevailed as they respond to the basic needs of the human being. It is practice itself that shows us that, both in the clinical and teaching aspects, enjoyment or the lack of it play a key role in learning. Child motivation to learn is, undoubtedly, fundamental. Because, in order to learn, the presence of desire is necessary